Operational SWAT+ model: advancing seasonal forecasting in the Limpopo River Basin - Chambel-Leitão, P.; Santos, F.; Barreiros, D.; Santos, H.; Silva, Paulo; Madushanka, Thilina; Matheswaran, Karthikeyan; Muthuwatta, Lal P.; Vickneswaran, Keerththanan; Retief, H.; Dickens, Chris; Garcia Andarcia, Mariangel (International Water Management Institute, 2024)
This "Operational SWAT+ Limpopo River Basin Seasonal Forecasting System" report outlines the development and implementation of an automated hydrological forecasting system using the Soil and Water Assessment Tool Plus (SWAT+). This system leverages publicly available global datasets and open-source modeling tools integrated within a custom developed automated system to predict seasonal water availability in the Limpopo River Basin (LRB). Key components include integrating the CHIRPS (Climate Hazards Group InfraRed Precipitation with Station data.) and ECMWF (European Centre for Medium-Range Weather Forecasts) precipitation data, comprehensive database management, and real-time monitoring scripts. The system provides accurate and timely water availability forecasts within the LRB to support operational decision making. Future directions focus on improving model calibration, incorporating additional weather variables, better representation of large reservoirs and irrigated areas, applying database optimization procedures, and transitioning to a Docker-based deployment on Amazon Web Services (AWS) for improved scalability and reliability. This SWAT+ operational seasonal forecasting system for the LRB marks a significant step towards bridging a key knowledge gap in the basin to support better decision making on multiple water uses and users including provision for environmental flows. This seasonal forecasting system as a part of the larger river basin Digital Twin is designed to influence effective water resource management in the Southern African region.